2017
DOI: 10.1161/circulationaha.116.021724
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Injury and Cerebral Blood Flow in Single Ventricles Throughout Staged Surgical Reconstruction

Abstract: Background Single ventricle patients experience a high rate of brain injury and adverse neurodevelopmental outcome, however, the incidence of brain abnormalities throughout surgical reconstruction and its relationship with cerebral blood flow, oxygen delivery and carbon dioxide reactivity remains unknown. Methods Single ventricle patients were studied with MRI scans immediately prior to bidirectional Glenn (pre-BDG), prior to Fontan and then 3–9 months after Fontan reconstruction. Results One hundred and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…MR findings in later life show striking deviations from normal in most people, with focal and multifocal abnormalities of different degrees. Findings show that non-acute ischemic changes such as atrophy and ventriculomegaly accumulate with staged surgical reconstruction [ 80 ]. Typically, spreading white matter abnormalities have been associated with cognitive impairment as well as gray matter abnormalities [ 81 , 82 ].…”
Section: Central Nervous System and Neurocognitive Functionmentioning
confidence: 99%
“…MR findings in later life show striking deviations from normal in most people, with focal and multifocal abnormalities of different degrees. Findings show that non-acute ischemic changes such as atrophy and ventriculomegaly accumulate with staged surgical reconstruction [ 80 ]. Typically, spreading white matter abnormalities have been associated with cognitive impairment as well as gray matter abnormalities [ 81 , 82 ].…”
Section: Central Nervous System and Neurocognitive Functionmentioning
confidence: 99%
“…Various predictors of neurodevelopmental outcomes in SVCHD have been established, including sociodemographic variables, disease characteristics, and aspects of the child's clinical course . One such clinical characteristic hypothesized to relate to subtle brain injury and associated neurodevelopmental abnormalities is the lower blood oxygen saturations that children with SVCHD experience from the prenatal period until the time of their Fontan operation and often, beyond . Hypoxemia is hypothesized to slow the pace of brain growth, particularly with regards to white matter, during gestation in SVCHD and contribute to increased inflammation and apoptosis as the brain develops during infancy, childhood, and adolescence .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] One such clinical characteristic hypothesized to relate to subtle brain injury and associated neurodevelopmental abnormalities is the lower blood oxygen saturations that children with SVCHD experience from the prenatal period until the time of their Fontan operation and often, beyond. 8 Hypoxemia is hypothesized to slow the pace of brain growth, particularly with regards to white matter, during gestation in SVCHD 9,10 and contribute to increased inflammation and apoptosis as the brain develops during infancy, childhood, and adolescence. 11 While hypoxemia during the stage-I palliation perioperative period has been shown to relate to poorer neurodevelopment in SVCHD [12][13][14] the unique contribution of chronic hypoxemia to altered neurodevelopment has been understudied in SVCHD.…”
Section: Introductionmentioning
confidence: 99%
“…One recent study examined cerebral blood flow throughout staged surgical reconstruction in single ventricle patients. The authors found that a higher cerebral blood flow correlated with a lower incidence of brain abnormalities [18].…”
mentioning
confidence: 95%
“…It has been shown that neonates with HLHS display delayed brain development and neurologic abnormalities even before cardiac surgery [7], which may contribute to persistent white matter maturation delay and reduction found in our study patients at two to three years. Hypoxic conditions, intracerebral hemorrhages, strokes and inflammatory episodes during staged surgical reconstruction can further delay brain maturation [18]. Two major factors predispose the developing white matter and the subcortical gray matter to injury from hypoxia-ischemia [23].…”
mentioning
confidence: 99%